Knowledge and knowing in South Africa: Making a case for the social sciences and the humanities - Morison, Tracy (PINS-Psychology in Society, 2025)
Jacklin, Heather & Vale, Peter (eds) (2009) Re-imagining the social in South Africa: Critique, theory and post-apartheid society. Pietermaritzburg: University of KwaZulu-Natal Press. ISBN 978-1-86914-179-0 pbk. Pages viii + 308 Congratulations on your Bachelor of Arts Degree. Now go on out there and be the best damn something-or-other you can be!” Quips like this, which imply that there is little value in the knowledge produced within the humanities and social sciences, are not unfamiliar to those who work in these disciplinary areas. In recent years the practical value of these disciplines has been increasingly questioned, as “hard” science and policy-oriented research has been prioritised over critically-oriented, qualitative, conceptual, or “merely” curiosity-driven research. Academics are increasingly required to respond to social and economic development initiatives, including the production of a capable workforce. Jacklin and Vale’s edited volume Re-imagining the social in South Africa responds to the global “threat” (p 78) and makes a case for “the indispensability of the humanities” (p 269) and social sciences.